Sign of APOBEC editing, purifying selection, frameshift, and in-frame nonsense mutations in the microevolution of lumpy skin disease virus - Desingu, Perumal Arumugam; Rubeni, T. P.; Nagarajan, K.; Sundaresan, Nagalingam R. (Frontiers in Microbiology, 2023)
The lumpy skin disease virus (LSDV), which mostly affects ruminants and causes huge-economic loss, was endemic in Africa, caused outbreaks in the Middle East, and was recently detected in Russia, Serbia, Greece, Bulgaria, Kazakhstan, China, Taiwan, Vietnam, Thailand, and India. However, the role of evolutionary drivers such as codon selection, negative/purifying selection, APOBEC editing, and genetic variations such as frameshift and in-frame nonsense mutations in the LSDVs, which cause outbreaks in cattle in various countries, are still largely unknown. In the present study, a frameshift mutation in LSDV035, LSDV019, LSDV134, and LSDV144 genes and in-frame non-sense mutations in LSDV026, LSDV086, LSDV087, LSDV114, LSDV130, LSDV131, LSDV145, LSDV154, LSDV155, LSDV057, and LSDV081 genes were revealed among different clusters. Based on the available complete genome sequences, the prototype wild-type Cluster-1.2.1 virus has been found in other than Africa only in India, the wild-type Cluster-1.2.2 virus found in Africa were spread outside Africa, and the recombinant viruses spreading only in Asia and Russia. Although LSD viruses circulating in different countries form a specific cluster, the viruses detected in each specific country are distinguished by frameshift and in-frame nonsense mutations. Furthermore, the present study has brought to light that the selection pressure for codons usage bias is mostly exerted by purifying selection, and this process is possibly caused by APOBEC editing. Overall, the present study sheds light on microevolutions in LSDV, expected to help in future studies towards disturbed ORFs, epidemiological diagnostics, attenuation/vaccine reverts, and predicting the evolutionary direction of LSDVs.